1993
DOI: 10.1086/285581
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Local Adaptation in Closely Adjacent Subpopulations of Northern Red Oak (Quercus rubra L.) Expressed as Resistance to Leaf Herbivores

Abstract: Many studies of herbaceous plant populations have illustrated the potential of adjacent subpopulations to adapt to local ecological conditions. However, the extent to which local adaptation on a small geographical scale can occur in outcrossing tree populations is not well understood. In this study, we reciprocally transplanted acorns from adjacent subpopulations of northern red oak (Quercus rubra L.) occupying north-, southwest-, and west-facing slopes within a 4-ha plot in a Missouri oak-hickory forest. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 13 publications
1
130
1
1
Order By: Relevance
“…In northern red oak, Sork et al (1993) showed that genetic differentiation for insect resistance occurs over a short distance, in response to environmental heterogeneity in the distribution of insects. However, our experiment did not allow us to attribute the morphological differentiation to an environmental or genetic origin.…”
Section: Discussionmentioning
confidence: 99%
“…In northern red oak, Sork et al (1993) showed that genetic differentiation for insect resistance occurs over a short distance, in response to environmental heterogeneity in the distribution of insects. However, our experiment did not allow us to attribute the morphological differentiation to an environmental or genetic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Host and parasite performance may be influenced by epigenetic maternal or conditioning effects such as acquired immunity. Furthermore, parasites or hosts may perform better in their home site because they have adapted to their local environment rather than to their local hosts and parasites, respectively (Rice, 1983;Sork et al, 1993;Roy, 1998). Natural parasite populations may also have their own coevolving hyperparasites, so parasites may be locally adapted only in the absence of these hyperparasites (Mopper et al, 1995).…”
Section: Environmental Heterogeneity: Yet Another Level Of Complicationmentioning
confidence: 99%
“…In most instances, the relative fitness of plants often was greatest for progeny from that locality. Sork et al (1993) found evidence for local adaptation in Quercus rubra for resistance to folivores in spite of high levels of gene flow across microhabitats. However, other studies have detected no evidence for adaptation to microsites (Cheplick 1988;Rice and Mack 1991;.…”
Section: Local Adaptationmentioning
confidence: 95%
“…Although these general issues have been addressed in many annual plant populations (Antonovics and Bradshaw 1970;Snaydon and Davies 1982), local adaptation and differentiation of adaptive traits in woody perennial plant populations has seldom been examined (but see Sork et al 1993), especially over relatively small spatial scales. Moreover, few studies examine genetic structure for more than one plant life-history stage (but see Tonsor et al 1993;Cabin 1996;Kalisz et al 2001).…”
mentioning
confidence: 99%